George W. Seifert Memorial Gymnasium under construction - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows the George W. Seifert Memorial Gymnasium on the Santa Clara University campus under construction. Handwritten on verso: "Santa Clara College Gymnasium. The $60,000 Geo. W. Seifert Memorial Gymnasium, dedicated Tues. eve. Jan. 29 by Basket ball game when this Mission varsity team lost by one point to the Olympic Club. Score 18 to 17 - 1100 people present. Photo by J. C. Gordon, San Jose".